(untitled) (Central Medical College Journal, 2026)
Background: B-type natriuretic peptide (BNP) is a key biomarker for cardiac stress and heart failure, yet elevated BNP levels also occur in hyperthyroidism despite the absence of overt heart disease. Because thyroid hormone excess can independently increase heart rate, cardiac workload, and BNP secretion, understanding this relationship is essential to prevent misdiagnosis of heart failure in thyrotoxic patients. Objective: This study aimed to evaluate plasma BNP levels in hyperthyroid patients compared to euthyroid individuals and to identify thyroid-related determinants of BNP elevation Methods: A cross-sectional study was conducted at the Department of Biochemistry, Bangladesh Medical University (BMU), including 90 adults aged 18–65 years: 45 with biochemically confirmed hyperthyroidism and 45 euthyroid controls. Individuals with cardiovascular, renal, or hepatic disease, pregnancy, or medications affecting thyroid or cardiac function were excluded. Plasma BNP, TSH, FT3, and FT4 were measured using micro particle enzyme immunoassay (MEIA). Statistical analysis involved group comparisons using t-tests and Mann–Whitney U tests, Spearman correlation, and multiple linear regressions to identify independent predictors of BNP levels. Results: Hyperthyroid patients had markedly higher BNP: median 215.50 pg/mL versus 34.25 pg/mL in controls (p<0.001). Both overt and subclinical hyperthyroid subgroups showed 6-fold and 5-fold higher BNP levels, respectively, than controls. Plasma BNP correlated positively with FT3 (free T3) and inversely with TSH. Multiple regression analysis identified FT3 as independent predictor of BNP levels. Conclusion: Elevated BNP in hyperthyroidism reflects subclinical cardiac stress from thyroid hormone excess rather than overt heart failure. Thyroid function assessment is essential when interpreting raised BNP to avoid misdiagnosis and guide appropriate management. Central Medical College Journal Vol 9 No 2 July 2025 Page: 105-110